Voicing in Ngamambo: A Descriptive perspective (Journal of the Digital Humanities Association of Southern Africa, 2023)
This paper describes voicing in Ngamambo, a semi Grassfields Bantu language in the North West Region of Cameroon. The language is classified under the Momo sub-language family (Eberhard, David M., Gray F. Simons and Charles D. Fenning, 2020). Ngamambo is unwritten, and research on the language is scanty. The only available literature on the language is by Asongwed & Hyman (1976)), Achiri-Taboh (2014) and Lem Atanga (2020) However, there has been some recent attempt by the Mbu Language Committee (MLC) to study the language. Interest in the study of Ngamambo stems from the imperative of undertaking a comprehensive description of the language. Preliminary research has revealed the existence of voicing in the language. Voicing is a process whereby the pronunciation of a word is influenced by one of the sounds. Data was obtained from Ngamambo native speakers (informants) over six months. The originality of this study resides in the fact that very little research has been carried out on the language. The authors of this paper discuss one aspect of the language and hope that subsequent studies will determine if voicing is also present in other Grassfields languages, especially the Momo sub-language family. The phonological process of voicing in Ngamambo has been observed when a voiceless sound becomes voiced depending on the environment. It is hoped that understanding this phenomenon would lead to a better understanding of voicing related to language learning.
Keywords: Voicing; Ngamambo; Standardisation